Pemetaan Kepuasan Kerja Karyawan Berbasis Customer Window Pada PT XYZ - Billah, Trisky Febrian Zallsa Billah; Wijaya, Jemi Cahya Adi; Cardias, Esa Riandy (Universitas Pendidikan Ganesha, 2024)
This study analyzes employee job satisfaction at PT XYZ, a tourism startup company. The company has been experiencing high turnover and absenteeism among employees in recent months. In an effort to understand this issue, the research adopts the Customer Window approach with a quantitative descriptive research design. Using employees as internal customers and mapping out their needs and desires. Through the Customer Window approach, this research aims to provide organizational insight into the needs of internal customers and motivate continu ous improvement. By increasing job satisfaction, it is hoped that employee turnover rates can be reduced. This research provides valuable insights for the human resource management of PT XYZ, with the aim of improving the quality of employees' working lives and achieving better job satisfaction. The results of this study show that indicators that fall into the A (Attention) quadrant are salary, recognition, training, working conditions and leader supervision, while those in the B (Bravo) quadrant are company policies, work itself, coworkers and social insurance. There were no indicators that fell into the C (Communicate) quadrant and D (Don't Worry Be Happy) quadrant. Keywords: Job Satifaction, Customer Window, Turnover